Validity and reliability of the Mini-Osteoarthritis Knee and Hip Quality of Life scale in Turkish population - Mehmet Tuncay Duruöz; Sevtap Acer Kasman; Halise Hande Gezer; Evrim Duruöz (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the validity and reliability of the Turkish version of the Mini-Osteoarthritis Knee and Hip Quality of Life (Mini-OAKHQoL) scale developed to assess the quality of life (QoL) in patients with knee and/or hip osteoarthritis. Patients and methods: Between May 2018 and May 2020, a total of 83 patients (11 males, 72 females; mean age: 58.1±10.0 years; range, 39 to 81 years) with knee and/or hip osteoarthritis were included. Demographic, clinical, and survey data (Mini-OAKHQoL, Nottingham Health Profile, Short Form-36, Western Ontario and McMaster Universities Osteoarthritis Index, Lequesne Index, and Visual Analog Scale of pain intensity) were recorded. Missing data, floor effect, and ceiling effect were calculated. For reliability analysis, internal consistency and test-retest reliability were discovered. Face, content, convergent, and divergent validities were applied. Results: Among the patients, 52 (62.65%) had knee osteoarthritis, 26 (31.32%) had hip osteoarthritis, and five (6.02%) had both. Mini-OAKHQoL had a good face and content validity. The average item completion rate was 96.9%, with the time needed to perform was about 4 min. None of the subscales of Mini-OAKHQoL presented floor or ceiling effect, with a good range of responses. The Cronbach alpha coefficients and intraclass correlation coefficient (ICC) analysis of the subscales ranged from 0.927 to 0.676 and 0.987 to 0.843, respectively. Regarding convergent validity, the physical activities, mental health, and pain subscales of Mini-OAKHQoL had moderate to high correlations with the topic-related subset of the other QoL surveys. There were no or weak correlations between Mini-OAKHQoL and non-QoL parameters, indicating its divergent validity. Conclusion: The Turkish version of Mini-OAKHQoL is a valid, reliable, simple, practical, accurate, completable, comprehensive, and disease-specific self-report instrument to assess QoL in patients with knee and/or hip osteoarthritis.